HASIL BELAJAR KETERAMPILAN MEMBACA PEMAHAMAN MENGGUNAKAN DEUTSCH INTERESSANT SEBAGAI BAHAN AJAR TAMBAHAN KELAS X - YULITASARI, YOAN (LATERNE, 2016)
The reason of this research is because the lack of student’s interest to learning Deutch especially in reading comprehention skill. Students tend to less excited when teacher ask them to read the text from their textbook. Therefore, it is necessary for an effective learning process with an alternative teaching material using the computer. One of the alternative computer based teaching material which proposed by Mahardika is Deutch Interessant. This research was conducted to determine the learning outcomes student of class X MIA 4 SMAN 1 Maospati using the alternative learning material which is Deutch Interessant. Formulation of the problem in this research is “ How is the student of class X MIA 4 SMAN 1 Maospati learning outcome in the reading comprehention skill with alternative computer based learning material the Deutch Interessant”. The aim of this research is to describe the learning outcome of reading comprehention skill with using Deutch Interessant as the computer based learning material. This research is a field research which all data source comes from the class X MIA 4 SMAN 1 Maospati student. The data of this research is learning outcome from the test result through the alternative learning material Deutch Interessant. The research procudure conducted through 2 phases which is namely learning and data analisys. Learning process of this reasearch conducted 3 times of teaching and learning process, at the last meeting students were given a test with Deutch Interessant to determine students learning outcomes. The result of the test is for futher analisys to knowing the learning outcome of student using Deutch Interessant. The data result of this research shows that Deutch Interessant is effective alternative learning material in Deutch reading comprehension skill learning. This can be seen from the test result of the student class X MIA 4 SMAN 1 Maospati that show 7 of 31 students are catagorized as very good, 20 of 31 are good, 2 of 31 students are catagorized as enough and 2 of 31 students catagorized as fail. Key wort : Deutsch Interessant